Modulators of MRP1 promoter in Neuroblastoma cell lines - Ghabriel, Myret Said (AUC Knowledge Fountain, 2014)
The long term goal of this research proposal is to further understand the transcriptional regulation of the MRP1 promoter in neuroblastoma cells. We are primarily focused on two possible mechanisms that might lead to the regulation of MRP1 expression: epigenetic modifications, in particular, gene promoter methylation and transcription factors namely the regulation by the methyl binding protein (MeCP2). Within the 5’ untranslated region of the MRP1 promoter is a CpG island that has the potential to be methylated, thus contributing to down regulation of MRP1 expression in drug sensitive neuroblastoma cells. Our goal is to determine if methylation status of the promoter region and subsequently the recruitment of MeCP2 that may play a role in the regulation of MRP1 expression. The methylation status of the promoter will be investigated using Methylation specific PCR and Bisulfite sequencing; while MeCP2 binding will be examined using Chromatin Immunoprecipitation.This project addresses a very important question, which is why neuroblastoma patients develop drug resistance. Identifying regulatory mechanisms for MRP1 expression can potentially help us to determine prognostic factors for drug resistance and further down the road lead to the development of better treatment strategies.